The population condition and availability of feed of cuscus in the Arfak Mountain Nature Reserve, West Papua - ANTON SILAS SINERY; CHANDRADEWANA BOER; WARTIKA ROSA FARIDA (Society for Indonesian Biodiversity, 2012)
Sinery AS, Boer C, Farida WR. 2012. The population condition and availability of feed of cuscus in the Arfak Mountain Nature Reserve, West Papua. Biodiversitas 13: 86-91. The cuscus is a pouched marsupial grouped in the Phalangeridae family, which is nocturnal, arboreal, herbivore, and in most cases the tail is prehensile. The animals are legally protected due to low reproduction, limited distribution area, and high rate of illegal hunting. The illegal hunting happened not only in the production forest areas but also in the reserve areas such as Nature Reserve of Arfak Mountain, directly or indirectly, affects the life quality of the ecosystem, mainly cuscuses population. Therefore, it is necessary to do efforts to have a better management of the region to ensure the sustenance of manycomponents in it. This research is aimed to know the population density of cuscus in Arfak Mountain Nature Reserve and carried out for two months. The method used was descriptive by using direct and indirect observation. The result shows that cuscuses existing in the Arfak Mountain conservation area were northern common cuscus (Phalanger orientalis), ground cuscus (Phalanger gymnotis) and common spotted cuscus (Spilocuscus maculatus). The biggest individual number is of P. orientalis with 39 individuals consisting of 18 males and 21 females, the second is of P. gymnotis with 10 individuals consisting of 4 males and 6 females, and the smallest is of S. maculatus with 9 individuals consisting of 4 males and 5 females. From the total of 58 cuscuses, there are 38 adult and 20 young cuscuses. There are 20 forest plant species identified as feed resources of cuscus in Arfak Mountain Nature Reserve. The parts of forest plant consumed by cuscus are fruits and young leaves. P. gymnotis also consumes small insects such as grasshopper. The cuscuses spread from lowland forest to highland forest (2,900 m asl.)